Implementasi Demand Side Management (DSM) Pada Instalasi Pengolahan Air PDAM Mulia Baru - mulyono mulyono (Sekolah Tinggi Teknik PLN, 2020)
The Mulia Baru Water Treatment Plant (IPA) is one of 6 Water Treatment Plants owned by the Ketapang Regency PDAM that is indicated to use a large amount of electrical energy. From the data obtained during one year (January to December 2017), the average monthly electricity consumption is 128,016,667 kWh with an average.Drinking Water Production Volume per month of 144,119,833 m3. Therefore the average Specific Energy Consumption (SEC) value for 2017 is 0.89. Through the application of the Peak Clipping and Strategic Concervation DSM program, a decrease in peak load occurs at a time interval between 17:00 and 22:00, in this condition a decrease in load of 0.47 (%).For greater savings, it is necessary to schedule the operation of large loads at peak load times.